GAME SCORING SUPPORTING OBJECTS MENGGUNAKAN AGEN CERDAS BERBASIS ARTIFICIAL INTELLIGENCE - Novita Putri, Astrid; Prathivi, Rastri (Jurnal Tr@nsForMat!ka, 2016)
Game are activity most structure, one that rdinary is done in fun and also education tool and help to develop practical skill, as training, education, simulation or psychological. On its developing current game have until 3D. In one game, include in First Person Shutter  necessary scoring  one that intent to motivate that player is more terpacu to solve game until all through,  on scoring  Super Marios game Boss, Compass does count scoring havent utilized Artifical Intelligent so so chanted, while player meet with supporting objects example ammor  ability really guns directly dead, so is so easy win. Therefore at needs a count scoring  interesting so more motivated in finishing problem Scoring accounting point for First Person Shutters game .This modelling as interesting daring in one game, since model scoring  one that effective gets to motivate that player is more terpacu in plays and keep player for back plays. Besides model scoring  can assign value that bound up with game zoom.On Research hits scoring this game will make scoring bases some criterion which is health Point, Attack point, Defence point, And  Magic  what do at have  supporting objects ,then in this research do compare two method are methodic statistic and Fuzzy. Result of this research 83,4 % on testings examination and on eventually gets to be concluded that fuzzys method in trouble finish time more long time but will player more challenging to railroad.